Population-based study of autoimmune hepatitis and primary biliary cholangitis in Germany: rising prevalences based on ICD codes, yet deficits in medical treatment - Sebode, Marcial; Kloppenburg, Angela; Aigner, Annette; Lohse, Ansgar W.; Schramm, Christoph; Linder, Roland (Zeitschrift für Gastroenterologie, 2020)
Background Population-based data on the prevalence of and real-life treatment for the autoimmune liver diseases (AILD), primary biliary cholangitis (PBC) and autoimmune hepatitis (AIH), are scarce, and such knowledge may help to improve patient care.Methods Data of 8.1 million individuals having health insurance with the “Techniker Krankenkasse,” the largest German health insurer, were analyzed with regard to the prevalence of and prescribed medication for AILD in Germany from 2011 until 2014. Patients with viral hepatitis B infection (HBV) and alcoholic liver cirrhosis (ALC) served as control groups. Case definition was based on ICD codes.Results The prevalences of PBC and AIH were 36.9/100 000 inhabitants (95 % CI: 35.6–38.2) and 23.0/100 000 inhabitants (95 % CI: 22.0–24.0) in 2014, respectively. The prevalences of AILD increased from 2011 to 2014 (for PBC by 31 % and for AIH by 29 %), with the largest increase for male patients with PBC. In contrast, the prevalence of HBV declined while that of ALC remained stable. The analysis of prescribed real-life treatment revealed considerable deviations from standard treatment recommendations. Specifically, in older patients with PBC or AIH, undertreatment was common.Conclusion The prevalence of PBC and AIH based on ICD codes is increasing in Germany. The analysis of real-life treatment in this large and population-based cohort points to the unmet need to improve the implementation of treatment guidelines for autoimmune liver diseases in the broader medical community.
Keywords: autoimmune hepatitis; primary biliary cholangitis; Germany; treatment; prevalence